2008
DOI: 10.1111/j.1365-263x.2008.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dilution on the in vitro erosive potential of a range of dilutable fruit drinks

Abstract: Increasing the dilution factor of dilutable fruit drinks within a range likely to be acceptable to the consumer may not effectively reduce their erosive potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 15 publications
(17 reference statements)
0
25
0
4
Order By: Relevance
“…26 One study investigated the effect of dilution on the erosive potential of dilutable fruit drinks. 27 The authors found that only a great increase in the dilution factor (1:15) of some of the tested products produced a statistically significant reduction in in vitro enamel erosion. The addition of water to an acceptable consumption level (1:3) did not diminish the beverages' erosive potential.…”
mentioning
confidence: 96%
“…26 One study investigated the effect of dilution on the erosive potential of dilutable fruit drinks. 27 The authors found that only a great increase in the dilution factor (1:15) of some of the tested products produced a statistically significant reduction in in vitro enamel erosion. The addition of water to an acceptable consumption level (1:3) did not diminish the beverages' erosive potential.…”
mentioning
confidence: 96%
“…70,73,83 Both regular and diet soft drinks have low pH (typically 2.4-3.5), high titratable acidity, and low calcium and phosphate concentrations, with the potential for erosion as well as cariogenicity. 42,73 Juices, regular and diet soft drinks can erode enamel, 73,[84][85][86] and enamel dissolution by soft drink acids can exceed the effects of bacterial acids from metabolism of sugars in the drink. 87 However, the potential of diet soft drinks (containing sugar substitutes) to increase caries risk is decreased markedly due to lack of sugar.…”
Section: Cariogenicity Of Sweet Drinks and Juicesmentioning
confidence: 99%
“…The buffering effects of the stimulated salivary fl ow may provide some protection against the erosive potential of acidic candy. 21,22,31 However, citric acid is a complex organic acid. At low pH values, citric acid provides protons which directly attack the mineral surface.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the demineralising effect of citric acid is exceptionally great and may even continue after the pH at the tooth surface has increased. 18,31,32 Our in vivo results are based on a single administration of candy spray to adult volunteers. However, candy sprays are frequently used by children during the day 26 and the volume of saliva in children is smaller than in adults.…”
Section: Discussionmentioning
confidence: 99%